Attendance to Psychiatric Urgencies and Emergencies in Primary Care: Challenges involved in caring (Research, Society and Development, 2022)
Objective: To identify the main challenges faced by higher education professionals working in primary care in the care of psychiatric urgencies and emergencies. Methodology: Qualitative study of an exploratory descriptive nature. The study was developed in two Health Matrix Units in Minas Gerais. The data collection period was from August to October 2020, based on interviews with professionals. Data analysis was performed using the IraMuTeQ Software. Results: From the data analysis, the following classes were originated: characterization of psychiatric urgency and emergency in the view of professionals; patient care; challenges encountered in care; and continuity of care for patients after the first visit. Obstacles were identified as: gaps in professional preparation, in the presence of the patients' family in the consultations, among others. Conclusion: The challenges highlighted in this study range from insufficient knowledge of professionals on the characterization of psychiatric urgency and emergency, passing through the difficulty in the management and effectiveness of the care offered, in addition to the scarcity of teamwork and deficient knowledge about the Network. of Psychosocial Care. Faced with this, professionals do not feel qualified to deal with psychiatric urgency and emergency situations and perceive themselves in an unfavorable context for qualified assistance.